Peningkatan Hasil Belajar Melalui Strategi Pembelajaran Index Card Match - Tri Sutisno; Nuzul Maghfiroh (TADRUSUUN: JURNAL PENDIDIKAN DASAR, 2024)
This research is based on poor student learning outcomes in lessons. The research in this thesis is to improve Al-Qur'an Hadith learning outcomes through the index card match learning strategy for class IV students at MI Hidayatun Najah Samiran Proppo Pamekasan-Madura. The type of research carried out was classroom action research, the subjects of this research were 12 class IV students at MI Hidayatun Najah. Teachers and researchers apply the index card method in learning to know the law of reading Idzhar and Ikhfa' in the Al-Qur'an Hadith subject, this can be seen from the results obtained by teachers and researchers by applying the index card method, the results can be seen in the pre-cycle stage and cycle I and cycle II stages. In each cycle, researchers apply the index card method when learning to read and write the Koran, and the changes in students after applying the index card method can be said to be successful because initially, the students were too lazy to study, students only talked to themselves and some played. Alone. However, after implementing the index card method, students are more serious and active when learning, this can be seen in the data from cycle I and cycle II, so the application of the index card method is very effective when used during learning.